Kontekstualisasi Pemikiran Waris Abdullah Saeed dalam Hukum Kewarisan di Indonesia - Suqiyah Musafa?ah (Islamica: Jurnal Studi Keislaman, 2015)
This article seeks to discuss the issue of inheritance in Indonesia and the solution offered through studying the Quranic verses of inheritance according to Abdullah Saeed. Saeed?s methodological approach is used as a tool of analysis to reconstruct the law of inheritance in Indonesia. On the one hand, Saeed?s theory of ?value hierarchy? is formulated in order to maintain the principle of Islam?s universality. On the other hand, this theory is applied in order for Islam to be valid for every time and place (s?lih li kull zam?n wa mak?n). Saeed?s theory of ?value hierarchy? consists of among others obligatory values, fundamental values, protectional values, implementational values, and instructional values. Based on Saeed?s theory of value hierarchy, the division of inheritance based of customary law (adat) called dumdum kupat (the portion of inheritance for son and that for daughter is the same) is valid and can be applied.